Britain : for learners of English : workbook. - O'Driscoll, James, ....- (Oxford : University Press, 2009)
Completely updated, Britain 2nd edition provides the historical and cultural background of British society and institutions such as the NHS and the BBC as well as an insight into the private daily life of the British people. Students are encouraged to think about the cultural issues raised and to make comparisons with their own culture. The companion Workbook to Britain contains quizzes, exercises, and topics for discussion which both test and develop your knowledge of Britain. Each unit corresponds to a chapter in the Student's Book.
Keywords: Engels; Groot-Brittannië.; Vreemde-talenonderwijs.